Early Birds, Late Risers, and Sleeping Beauties : Bank Credit Growth to the Private Sector in Central and Eastern Europe and in the Balkans - Hollar, Ivanna; Cottarelli, Carlo; Dell'Ariccia, Giovanni (Washington, D.C. : International Monetary Fund, 2003)
Following a period of privatization and restructuring, commercial banks in Central and Eastern Europe and, more recently, in the Balkans have rapidly expanded their lending to the private sector. This paper describes the causes of this expansion, assesses future trends, and evaluates its policy implications. It concludes that bank credit to the private sector is likely to continue rising faster than GDP in the next few years throughout the region, picking up also in countries where so far it has been stalled. Although this growth should be regarded as a structural and positive development, policymakers will have to evaluate carefully its implications for macroeconomic developments and financial stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet